AUTHORITY AND COORDINATION OF THE CORRUPTION ERADICATION COMMISSION AND THE STATE POLICE OF THE REPUBLIC OF INDONESIA IN INVESTIGATIONS OF CORRUPTION CRIMES IN INDONESIA - Charlie Y Usfunan (Khairun Law Journal, 2023)
The aim of this research is to determine the limits of the authority of the Corruption Eradication Committee and the National Police in handling criminal acts of corruption in Indonesia because in practice there are often clashes between the two authorized institutions, namely the Corruption Eradication Commission and the Indonesian National Police, in handling criminal acts of corruption.This research is normative legal research that uses a statutory approach and a legal concept analysis approach. The data sources used in this research come from primary data sourced from statutory regulations and secondary data sourced from literature.From the results of this research, it can be concluded that the authority of the Corruption Eradication Commission as an institution for eradicating corruption is delegated authority, while the authority of the National Police in eradicating corruption is attribution authority. However, the Corruption Eradication Commission (KPK) is a super body institution in handling criminal acts of corruption, especially in the investigation process. In relation to coordination, the Corruption Eradication Commission has special authority that is not owned by the National Police, however, the Corruption Eradication Committee still coordinates with the National Police in carrying out its duties and authority.